Materials use trends of Malaysian furniture exporters in Klang Valley - Ong, Sin Lei (2019)
The objective of this study were to identify the most common materials used and the reasons for the popularity of these commonly used raw materials in Malaysian furniture exports. Secondary data published from Department of Statistic from 2010 – 2017 is collected to fulfil the first objective and questionnaire survey was carried out to gather information from the 25 largest furniture manufacturers and exporters in the Klang Valley. The results indicated over 80% of the furniture products are made from wooden furniture. Cost is the most important reason of the raw material being used followed by availability, profitability, market demand government policy and lastly technology used in processing raw material. The results would be beneficial to supplier of furniture manufacturer as to achieve higher performances in their businesses.